Curva tensional ocular fisiológica diária e proposição da mini curva correlacionadas com os níveis séricos de cortisol em equinos adultos da raça crioula - Flores, Fabiano da Silva (2025)
Intraocular pressure (IOP) measurement is important for the diagnosis of eye diseases, monitoring and evaluation of treatment. Due to the action of several factors on IOP, performing tonometry throughout the day and night reveals its normal variation and obtains the daily physiological ocular tension curve (CTD). Thus, the objective was to present the normal physiological values and physiological peaks of IOP during 24 hours, and thus establish the CTD and the mini curve, for the equine species, in addition to verifying whether there is a relationship between IOP and serum cortisol levels in adult horses of the Crioula breed. A total of 864 average IOP measurements were performed with the rebound tonometer (TonoVet®), in both eyes, every 2 hours, during the 24 hours of the day, in the right and left eyes, respectively, and blood was collected after measuring the pressures. In total, 12 healthy horses used for equestrian sport, aged between five and fifteen years, were used. Previously, for the selection of animals, a complete ophthalmological examination was performed, and only animals without ocular and systemic alterations were selected. The mean value of intraocular pressure in both eyes for all evaluations was 25.87 ± 4.39 mmHg. The mean IOPs observed in the right and left eyes were 25.88 ± 4.42 mmHg and 25.86 ± 4.45 mmHg, respectively. Thus, there was a correlation between the general pressure means (p=0.893) over the 24 hours, when compared at the same time, but with a statistical difference when comparing the means between times of maximum and minimum values (p=0.03). The study determined the daily ocular tension curve and the mini curve, with it being important to measure it at three times, minimum peak at 5:00 am (22.97 mmHg), maximum peak at 11:00 am (32.11 mmHg) and values closest to the general average at 11:00 pm (25.93 mmHg). Furthermore, there was no statistically correlation between intraocular pressure and serum cortisol levels in the species.